The Considerations Analysis of Different PTUN and MA Decisions which are Detrimental to Insurance Consumers - Kusumah, Rio Hadi; Haryanto, Imam (Universitas Islam Sultan Agung, 2024)
This study discusses the differences between the Supreme Court (MA) Decision Number 647 K/Pdt.Sus-Pailit/2021 and the Jakarta PTUN Decision Number 475/G/2023/PTUN.JKT related to the case of PT Asuransi Jiwa Kresna (Kresna Life) and its impact on the protection of insurance consumer rights. This study uses a normative legal method with a statute approach and a case study approach. Data were collected through a literature study covering laws and regulations, court decisions, and expert opinions related to the insurance industry. In general, the MA Decision annulled the determination of the Suspension of Debt Payment Obligations (PKPU) filed by individual creditors, stating that the settlement of obligations must be supervised by the Financial Services Authority (OJK) through a liquidation mechanism. Conversely, the Jakarta PTUN annulled the decision to revoke Kresna Life's business license by the OJK, thus prolonging legal uncertainty for policyholders. As a result of these conflicting decisions, the liquidation process that should guarantee the return of claim funds to policyholders is hampered, and consumer rights are difficult to realize. The results of the study show that the differences in these decisions weaken the authority of the OJK as a regulator, as stipulated in Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK) and POJK Number 28/POJK.05/2015 concerning the liquidation of insurance companies. This reduces public trust in the insurance industry and increases the risk of financial loss for policyholders.